EFFECT OF VOLATILE AND TARGET LITHOLOGY ON THE GENERATION AND EMPLACEMENT OF IMPACT CRATER FILL AND EJECTA DEPOSITS ON MARS - Osinski G.R. (My University, 2006)
Impact cratering is an important geological process on Mars and the nature of Martian impact craters may provide important information as to the volatile content of the Martian crust. Terrestrial impact structures currently provide the only ground-truth data as to the role of volatiles and an atmosphere on the impact-cratering process. Recent advancements, based on studies of several well-preserved terrestrial craters, have been made regarding the role and effect of volatiles on the impact-cratering process. Combined field and laboratory studies reveal that impact melting is much more common in volatile-rich targets than previously thought, so impact-melt rocks, melt-bearing breccias, and glasses should be common on Mars. Consideration of the terrestrial impact-cratering record suggests that it is the presence or absence of subsurface volatiles and not the presence of an atmosphere that largely controls ejecta emplacement on Mars. Furthermore, recent studies at the Haughton and Ries impact structures reveal that there are two discrete episodes of ejecta deposition during the formation of complex impact craters that provide a mechanism for generating multiple layers of ejecta. It is apparent that the relative abundance of volatiles in the near-surface region outside a transient cavity and in the target rocks within the transient cavity play a key role in controlling the amount of fluidization of Martian ejecta deposits. This study shows the value of using terrestrial analogues, in addition to observational data from robotic orbiters and landers, laboratory experiments, and numerical modeling to explore the Martian impact-cratering record. © The Meteoritical Society, 2006.